Reducing peak-to-average power ratio of filtered non-orthogonal multiple access and new radio 5g waveforms using hybrid partial transmit sequence-companding technique - Arun Kumar; Karthikeyan Rajagopal; Nishant Gaur; Aziz Nanthaamornphong (ETRI Journal)
For fifth-generation (5G) and beyond 5G communications, filtered nonortho-gonal multiple access (F-NOMA) can be used as a waveform contender. Filtering-based waveform frameworks provide suppression of out-of-band emission (OOBE) and asynchronous transmission. For new types of wave-forms, a high peak-to-average power ratio (PAPR) remains a challenge. A high PAPR in multicarrier systems can be efficiently mitigated by applying partial transmit sequence (PTS). Combining PAPR reduction techniques can improve the transmission efficiency by nonlinearly scaling the signal amplitudes before transmission and inversely scaling them at the receiver. We propose a hybrid technique that combines PTS and companding to reduce the PAPR in an F-NOMA system. Conventional nonorthogonal multiple access (NOMA) is compared with F-NOMA, and systems with and without the hybrid technique are examined regarding metrics including the power spectral density, bit error rate (BER), and computational complexity. Compared with NOMA, simulation results show that F-NOMA using the proposed technique improves the PAPR and OOBE while preserving the BER performance of F-NOMA.